An Integrated Gut Microbiota and Network Pharmacology Study on Fuzi-Lizhong Pill for Treating Diarrhea-Predominant Irritable Bowel Syndrome - Zhang Zhen; Zhang Zhen; Lin Xia; Huang You; Zhou Jingwei; Yang Shasha; Wei Xinyi; Lai Wenjing; Zhang Xin; Fu Chaomei (Frontiers Media S.A., 2021)
Diarrhea-predominant irritable bowel syndrome (IBS-D) is one of the most common chronic functional gastrointestinal diseases with limited treatments. Gut microbiota play an important role in chronic gastrointestinal diseases. In traditional Chinese medicine (TCM), Spleen-Yang deficiency (SYD) is one of the root causes of IBS-D. Fuzi-Lizhong pill (FLZP) is well known for its powerful capacity for treating SYD and has a good clinical effect on IBS-D. However, the mechanism of FLZP on the gut microbiota of IBS-D has not been fully clarified. Our present study aimed to reveal the mechanism of FLZP regulating gut microbiota of IBS-D. The body mass, CCK, MTL, and Bristol fecal character score were used to verify the establishment of the IBS-D model. IL-6, TNF, IL-1β, and IFN-γ were crucial targets screened by network pharmacology and preliminarily verified by ELISA. Eighteen gut microbiota were important for the treatment of IBS-D with FLZP. Bacteroidetes, Blautia, Turicibacter, and Ruminococcus_torques_group were the crucial gut microbiota that FLZP inhibits persistent systemic inflammation in the IBS-D model. Lactobacillus is the crucial gut microbiota that FLZP renovates intestinal immune barrier in the IBS-D model. In summary, FLZP can affect bacterial diversity and community structures in the host and regulate inflammation and immune system to treat IBS-D.